تأثير العدوى الميكانيكية بفيروس موزاييك الخيار في إنتاجية بعض أصناف البندورة في بيت بلاستيكي - راعي سليم (Latakia University Journal -Biological Sciences Series, 2019)
أثبتت دراسة العدوى الميكانيكية بعزلة محلية من فيروس موزاييك الخيار تأثيراً سلبياً في متوسطات أطوال الأصناف الآتية: صيدا, ريدوينغ, هدى, وروزانا مقارنة بشواهدها وبفروق معنوية. وأشار التحليل الإحصائي إلى وجود فروق معنوية عند المقارنة بين الأصناف, مع بعضها بعضاً, من حيث التأثير في متوسطات أطوالها باستثناء روزانا مع هدى. سببت العدوى الفيروسية تقزماً لنباتات أصناف البندورة المدروسة صيدا, ريدوينغ, هدى, وروزانا مقداره 24.3%, 14.48%, 14.25%, و13.79% على التوالي. وانخفض متوسط عدد الثمار وبفروق معنوية عند الصنفين صيدا وروزانا وتأثر متوسط الوزن الكلي لثمار الأصناف الأربعة وبفروق معنوية بين نباتات المعاملة ونباتات الشاهد. إن أكثر الأصناف حساسية للفيروس المدروس هو الصنف صيدا. This study of mechanical inoculation with local isolate of Cucumber mosaic cucomovirus has revealed a significant negative effect on plant height of tomato varieties; Saida, Hoda, Red wing, and Rossana in comparison to their control. Statistical analysis has proved significant differences between varieties, especially the effect on means of tomato plant height except Rosanna and Hoda. The Studied virus has caused stunting on studied tomato varieties Saida, Hoda, Red wing and Rosanna 24.3%, 14.48%, 14.25%, and 13.79% respectively. The mean of fruit numbers has significantly decreased in the varieties Saida and Rosanna. The mean of total fruit weight of the studied varieties has been affected with significant differences in comparison with controls. Saida variety was more sensitive to the studied viral infection.